Power Efficiency Enhancement in High-Boost Three-Phase Split Source Inverters - Ibrahim, Safaa; Hamad, Samir A.; Mansour, Arafa S.; Zaky, Mohamed S.; Abdel-Samei, Abdel-Gawad A.; Lotfy, Mostafa Wageh (Engineering, Technology & Applied Science Research, 2025)
This paper presents the design, analysis, and verification of a Split-Source Inverter (SSI) topology aimed at achieving efficient high-boost DC-AC power conversion with minimized power losses. The proposed design integrates an advanced control strategy utilizing Space Vector Modulation (SVM) to ensure clean sinusoidal output with minimal harmonic distortion. The study offers an in-depth examination of the SSI's operating principles, power loss mechanisms, and the distribution of losses across power switches, alongside optimization techniques to improve overall performance. Simulation results under diverse operating conditions validate the SSI's capability to deliver stable and efficient operation. Additionally, experimental implementation using a prototype validated the theoretical and simulation results, demonstrating the inverter's reliable operation and effective thermal management. Key findings underscore the significant advantages of the proposed SSI topology, including its compact design and superior performance compared to the quasi-Z-Source Inverter (q-ZSI). Specifically, the SSI reduces switching losses from 22% to 20% and decreases conduction losses from 42% to 38%, demonstrating enhanced efficiency, energy management, and applicability to diverse fields such as renewable energy systems and industrial drives.